Role of echocardiographic dyssynchrony parameters in predicting response to cardiac resynchronization therapy. Issue 11 (November 2015) - Maffè, Stefano; Paffoni, Paola; Dellavesa, Pierfranco; Perucca, Antonello; Kozel, Daniela; Paino, Anna M.; Cucchi, Lorenzo; Zenone, Franco; Bergamasco, Luca; Pardo, Nicolò Franchetti; Signorotti, Fabiana; Baduena, Lara; et al.
<x xml:space="preserve">Abstract</x> Aims In the present study, we compare different echocardiographic cardiac dyssynchrony parameters, both of intraventricular and interventricular dyssynchrony, in order to predict response to cardiac resynchronization therapy (CRT). Methods and results In a population of 77 heart failure patients scheduled for CRT, we measured the interventricular mechanical delay (IVMD) and we analyzed six different parameters of intraventricular dyssynchony: the tissue Doppler imaging (TDI) septum-lateral wall delay, the systolic dyssynchrony index; the three-dimensional SD of the time to reach minimum systolic volume for 16 left ventricular segments (3D-SDI); the speckle-tracking radial, circumferential and longitudinal dyssynchrony. At 6 months of follow-up, 61 (79%) patients were responders (⩽15% in left ventricular end-systolic volume). On baseline analysis, 3D-SDI, radial strain, longitudinal strain and circumferential strain and IVMD were significantly higher in responder group (10.8 ± 3.9 vs. 7.6 ± 1.8% for 3D-SDI; P = 0.003; 212 ± 91 vs. 125 ± 36 ms for radial strain, P = 0.0003; 185 ± 83 vs. 134 ± 53 ms for longitudinal strain, P = 0.02; 190 ± 80 vs. 130 ± 54 ms for circumferential strain, P = 0.006; 45 ± 21 vs. 30 ± 20 ms for IVMD; P = 0.01). On univariate and multivariate analysis, only IVMD was significantly associated with a complete echocardiographic response to CRT. 3D-SDI and radial strain present the better values of sensitivity and specificity, overall if associated to an evaluation of IVMD (sensitivity 76%, specificity 88%, for 3D-SDI + IVMD; sensitivity 80% and specificity 85% for radial strain + IVMD). Conclusion The novel parameters, such as 3D-SDI and speckle-tracking (particularly radial strain), offer better diagnostic accuracy in identifying patients who are responders to CRT. The addition of the contemporary parameter of IVMD improves the diagnostic accuracy.